2011
DOI: 10.1021/ja201779d
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Colloidal Mesoporous Nanoparticles with Ethenylene-Bridged Silsesquioxane Frameworks

Abstract: Aqueous colloidal mesoporous nanoparticles with ethenylene-bridged silsesquioxane frameworks with a uniform diameter of ∼20 nm were prepared from bis(triethoxysilyl)ethenylene in a basic aqueous solution containing cationic surfactants. The nanoparticles, which had higher hydrolysis resistance under aqueous conditions, showed lower hemolytic activity toward bovine red blood cells than colloidal mesoporous silica nanoparticles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 178 publications
(161 citation statements)
references
References 39 publications
(18 reference statements)
9
148
0
2
Order By: Relevance
“…Furthermore, the key event being considered responsible for the hemolysis is the interaction with RBC membranes, while secondary metabolic effects induced by the presence of porous silica nanoparticles are being neglected by the approaches reported so far in the literature. [14][15][16]18 As it has been recently reported, 21,22,27 the dynamic interaction phenomenon occurring in biological media in which biomolecules may adsorb on a nanoparticle surface (and also desorb from it) results in a corona coating (illustrated in Figure 3b) that will play a key role in all further biological effects manifested in a living organism. In a more specific case, the influence of these coatings on Results from the N 2 adsorption branch using the BET method; b evaluated through the single-point value adsorbed at the relative pressure (P/ Positive and negative controls were taken with DI water and PBS.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Furthermore, the key event being considered responsible for the hemolysis is the interaction with RBC membranes, while secondary metabolic effects induced by the presence of porous silica nanoparticles are being neglected by the approaches reported so far in the literature. [14][15][16]18 As it has been recently reported, 21,22,27 the dynamic interaction phenomenon occurring in biological media in which biomolecules may adsorb on a nanoparticle surface (and also desorb from it) results in a corona coating (illustrated in Figure 3b) that will play a key role in all further biological effects manifested in a living organism. In a more specific case, the influence of these coatings on Results from the N 2 adsorption branch using the BET method; b evaluated through the single-point value adsorbed at the relative pressure (P/ Positive and negative controls were taken with DI water and PBS.…”
Section: Resultsmentioning
confidence: 95%
“…Firstly, it was observed that silanol groups on mesoporous silica structures induce less hemolytic effect compared to rigid spherical nanoparticles possibly due to shape-induced effects, which determine the spatial availability of silanols on the nanoparticle-cell interface. 13 Further, it was observed that: (i) smaller Stöber silica nanoparticles (24 nm) induce a pronounced hemolytic effect when compared with bigger ones (263 nm); 14 (ii) nanostructures with high aspect ratio (nanorods) are more cytotoxic than spherical nanoparticles; 15 (iii) mesoporous silica nanostructures (MSNs) with ordered pores (MCM-41) induce a stronger hemolytic effect compared with non-ordered; 14 (iv) small mesoporous nanoparticles (20 nm) consisted of ethenylenebridged silsesquioxane present very low toxicity 16 and (v) polymers such as PEG (polyethylene glycol) can be used to coat particles in order to greatly reduce the hemolysis. 17 Furthermore, an extensive assessment of the interaction of bare and functionalized porous silica nanomaterials with RBCs concluded that SBA-15-type MSNs cause the deformation of RBCs and consequently lead to their disruption.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Kuroda et al reported highly dispersed mesoporous nanoparticles with silsesquioxane frameworks and ethenylene-bridged groups. 202 The particle size was extremely uniform, with an average diameter of 20 nm.…”
Section: Novelties In Surfactant-templated Mesoporous Materialsmentioning
confidence: 99%
“…However, colloidal mesoporous organosiloxane nanoparticles can be prepared by using only bridged silsesquioxanes. Our group has succeeded in preparing colloidal mesoporous organosiloxane nanoparticles by using bis(triethoxysilyl)ethenylene or ethynylene as a single source (Figure 16(left)), 158 though the adsorption isotherm did not clearly show the presence of mesopores. Our ongoing research shows that an increase in the pH of the precursor solution may lead to the formation of clearer mesopores in the system.…”
Section: Preparation Of Colloidal Msns By Using Bridgedmentioning
confidence: 99%